2003
DOI: 10.1080/1042819031000110937
|View full text |Cite
|
Sign up to set email alerts
|

Letter to the Editor

Abstract: Primary bone lymphoma (PBL) is a rare entity and comprises about 5% of all extranodal non-Hodgkin's lymphomas (NHL) and 7% of all primary bone tumors. To date there is no consensus about the optimal treatment for PBL. We retrospectively reviewed all cases of PBL treated at Hospital São Paulo, Brazil, over a 10-year-period (January 1992-January 2002). Medical records of 7 patients with PBL were reviewed and information on age at diagnosis, sex, NHL clinical staging (CS), treatment and response to treatment were… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2013
2013
2017
2017

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 6 publications
0
2
0
Order By: Relevance
“…According to Coley’s criteria [8], primary bone lymphoma should have: 1) a primary focus in a single bone; 2) positive histological diagnosis; and 3) no evidence of distant soft tissue or distant lymph node involvement. Regional lymph node involvement at diagnosis is not considered as an exclusion criterion [9,10]. Recently, multiple bone involvement was also recognized as primary bone lymphoma, as long as the other 2 criteria are met [9].…”
Section: Discussionmentioning
confidence: 99%
“…According to Coley’s criteria [8], primary bone lymphoma should have: 1) a primary focus in a single bone; 2) positive histological diagnosis; and 3) no evidence of distant soft tissue or distant lymph node involvement. Regional lymph node involvement at diagnosis is not considered as an exclusion criterion [9,10]. Recently, multiple bone involvement was also recognized as primary bone lymphoma, as long as the other 2 criteria are met [9].…”
Section: Discussionmentioning
confidence: 99%
“…Radiotherapy achieved high levels of local control (80–100%) but was followed by a high late relapse rate (50%) [5]. Then different CMT schedules of chemotherapy and radiotherapy were proposed [7, 15, 16, 22, 23]. It has been shown that anthracycline-based therapy improves the response rate and prolongs OS of patients with localized lymphomas [23].…”
Section: Discussionmentioning
confidence: 99%